Baiаo as a component of soundscapes of Brazil: guitar reconstructions of the genre - Filatova, Tetiana (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
The relevance of the article. The coverage of the pages of the guitar work of Brazilian composers seems to be relevant for the search for new horizons of the modern repertoire of South American music in the context of actualize genre and style projections of soundscapes of this big country and regional music traditions. Main objective of the study is to reveal in guitar music the rhythmic and intonation-melodic archetypes of baiao as the titular genre and an important component of the Brazilian soundscape. The novelty of the article lies in the introduction into the Ukrainian musicological circulation the analysis of Latin American guitar works, which represent the specifics of this genre phenomenon. The methodology includes interdisciplinary approaches and methods of cultural, musicological, historical, comparative, systemic, structural and functional analysis to determine the genre and style elements of folk music, its reflection in culture and academic guitar works. Results and conclusions. Brazilian baiao, as one of the leading genres of the country’s musical culture, was first developed in its southeastern regions - Bahia and Pernambuco. During the last century, it acquired the status of an emblem of local domestic and concert creativity. Based on ritualistic and ceremonial ancient traditions, imprinted in the public dance processions of today, baiao is the personification of a certain musical archetype. It consists of recognizable timbral features of the Brazilian sound sonotype (Indian flutes, Angolan drums, Brazilian guitars) and is preserved in a solo guitar performance thanks to the techniques of sound imitation. The character of Brazilian timbres reflects the soundscapes of the rural and urban hinterland of the southeastern regions. The development of the genre’s ethnic roots in the conditions of new composer incarnations was facilitated by the musical aesthetics of the Movimento Armorial. Its manifesto was: the reflection of local national traditions in combination with the language resources of the baroque musical "dictionary" of European (Iberian) origin, the mixing of ancient modal elements and composer’s techniques, as well as the involvement of elements of modern academic and jazz cultures. The result of these processes is a wide stylistic amplitude of artistic embodiments of the genre in the guitar work of Latin American and European composers — A. Madureira, P. Bellinati, E. Gismonti, C. Aguirre, R. Dyens, M. Duplessy and others. The baiao rhythm (a sharp syncopated binary pulse) and the baiao mode (Lydian-mixolydian with other mixed variations of mode formation) are clearly defined in all analyzed works. Fast tempos generate powerful energy of a sonorous, motor-dance wave, which reproduces the soundscapes of the huge "musical continent" with its purely Brazilian flavor